The Effects Of Antimicrobial And Physical Properties Of Denture Soft Reline Material - et.al, Yu-Ri Choi (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Candida albicans(C. albicans) is one of the bacteria that resides in the oral cavity, and the ones living in medical and commercial denture resins, commonly cause diseases. Therefore, this study was conducted to confirm the antibacterial activity of C. albicans using a denture base resin containing peony extract with antibacterial properties. For the antibacterial effect, optical density and confocal laser microscopy were used. Contact angle measurements and color change measurements were performed to confirm the physical change of the material added with the antibacterial agent to the denture reline resin. As a result of the antibacterial test, the experimental group exhibited antibacterial activity against C. albicans. Compared to the optical density results, the results of the experimental group showed a significant difference. As a result of Fluorescent images showing (confocal laser microscope), the control group showed a lot of live bacteria, no bacteria appeared in the experimental group. All group did not show any physical changes. As a result of the contact angle measurement, the surface of the experimental group was changed to hydrophilic. In addition, there was no change in the color of the denture reline resin containing peony extract. In conclusion, it was confirmed that the peony extract contained antibacterial activity of the denture resin, and further studies should be conducted on various bacteria for denture base resin disinfection.